2022
DOI: 10.3855/jidc.16853
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication with antibiotics and awareness of antibiotic resistance among population in Arar city, Saudi Arabia

Abstract: Introduction: Self-medication with pharmaceutical products can be defined as the use of these products without a medical prescription, and the production, distribution, and sale of these products are the client’s responsibility, while they think it is within rational usage. Among these products, antibiotics remain the most serious problem leading to the spread of antibiotic resistance, with consequences of increased morbidity, mortality, and extended hospital stays. Methodology: This is a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…A previous investigation reported that individuals predominantly relied on their relatives, friends, and previous prescriptions as sources of information when attempting SM [16]. This study demonstrated relatively similar results, where the primary sources of information on SM with antibiotics were family/friends (21.6%), pharmacists (20.5%), internet/social media (18.7%), previous prescriptions (15.8%), and instruction sheets in medicine (6.9%).…”
Section: Discussionsupporting
confidence: 72%
“…A previous investigation reported that individuals predominantly relied on their relatives, friends, and previous prescriptions as sources of information when attempting SM [16]. This study demonstrated relatively similar results, where the primary sources of information on SM with antibiotics were family/friends (21.6%), pharmacists (20.5%), internet/social media (18.7%), previous prescriptions (15.8%), and instruction sheets in medicine (6.9%).…”
Section: Discussionsupporting
confidence: 72%
“…1 A study revealed that 81.4% of the respondents believed that antibiotic resistance occurs when the body develops a resistance to antibiotics and ceases to function properly. 19 When asked what they believe could be done to decrease antibiotic resistance, 88.08% (n=650) of respondents believe that antibiotics campaigns can alter community habits.…”
Section: Discussionmentioning
confidence: 99%
“…While our research yielded similar results to the first study, with 71.41% (n=527) of respondents stating that they complete the course as instructed; the first study had a larger sample size. 18 The presence of expired pharmaceuticals in the home can increase the risk of toxicity, suicide, and accidental poisoning of children, 19 whereas the presence of unused antibiotics indicates antibiotic misuse and may increase the likelihood of antibiotic resistance. 20 Storage at an improper temperature could have negative consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This includes self-medication due to lack of prescription obligation, incorrect dosage, missed doses, and reuse of antibiotics from past prescriptions [3,4]. Studies from some Arabic countries showed high rates of inappropriate use of antibiotics as demonstrated by the high rates of antibiotics self-medication, which ranged from 44 to 77.5% [5][6][7][8][9]. The Gulf Cooperation Council countries, which includes Saudi Arabia, the United Arab Emirates, Kuwait, Qatar, Oman, and Bahrain, have a high rate of Gram-negative bacterial resistance, such as extended-spectrum beta-lactamases, carbapenem-resistant Enterobacterales, Pseudomonas aeruginosa, and Acinetobacter baumannii [10][11][12].…”
Section: Introductionmentioning
confidence: 99%